Beyond tenure: reviewing the welfare and ministry of retired pastors in Zimbabwe - Tagwirei, Kimion (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2022)
Increasing numbers of retired pastors have been struggling with welfare and ministry challenges upon retirement in Zimbabwe for decades. Scholarship on the well-being and ministry of retired pastors in Zimbabwe is scanty. Thus, this study explored problems that the pastors of the Assemblies of God Back to God (AOG BTG) face after retirement. Applying Osmer’s methodology, this paper addressed what the church and pastors could do to prepare for, and deal with their difficulties. It proposed that the church could rebuild its economic sustainability to resource pastors to effectively prepare for retirement, adopt pension plans and support different ministries that they could engage in. It also recommended that the pastors can embrace tent–making to sustain their welfare, new ministries, and other needs and wants after tenure.